Prenatal vitamin D status and offspring's growth, adiposity and metabolic health: a systematic review and meta-analysis. Issue 3 (11th January 2018) - Santamaria, Christina; Bi, Wei Guang; Leduc, Line; Tabatabaei, Negar; Jantchou, Prévost; Luo, Zhong-Cheng; Audibert, François; Nuyt, Anne Monique; Wei, Shu Qin
Abstract: In this systematic review and meta-analysis of observational studies, we aimed to estimate the associations between prenatal vitamin D status and offspring growth, adiposity and metabolic health. We searched the literature in human studies on prenatal vitamin D status and offspring growth in PubMed, up to July 2017. Studies were selected according to their methodological quality and outcomes of interest (anthropometry, fat mass and diabetes in offspring). The inverse variance method was used to calculate the pooled mean difference (MD) with 95 % CI for continuous outcomes, and the Mantel–Haenszel method was used to calculate the pooled OR with 95 % CI for dichotomous outcomes. In all, thirty observational studies involving 35 032 mother–offspring pairs were included. Vitamin D status was evaluated by circulating 25-hydroxyvitamin D (25(OH)D) level. Low vitamin D status was based on each study's cut-off for low 25(OH)D levels. Low prenatal vitamin D levels were associated with lower birth weight (g) (MD −100·69; 95 % CI −162·25, −39·13), increased risk of small-for-gestational-age (OR 1·55; 95 % CI 1·16, 2·07) and an elevated weight (g) in infant at the age of 9 months (g) (MD 119·75; 95 % CI 32·97, 206·52). No associations were observed between prenatal vitamin D status and other growth parameters at birth, age 1 year, 4–6 years or 9 years, nor with diabetes type 1. Prenatal vitamin D may play a role in infant adiposity and accelerated postnatal growth. The effects of prenatal vitamin D on long-term metabolic health outcomes in children warrant future studies.